2004
DOI: 10.1128/aem.70.4.1883-1894.2004
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Ecology of Fresh Sausages and Characterization of Populations of Lactic Acid Bacteria by Molecular Methods

Abstract: In this study, a polyphasic approach was used to study the ecology of fresh sausages and to characterize populations of lactic acid bacteria (LAB). The microbial profile of fresh sausages was monitored from the production day to the 10th day of storage at 4°C. Samples were collected on days 0, 3, 6, and 10, and culture-dependent and -independent methods of detection and identification were applied. Traditional plating and isolation of LAB strains, which were subsequently identified by molecular methods, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
1
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(133 citation statements)
references
References 38 publications
11
113
1
8
Order By: Relevance
“…Noteworthy is the specificity of the association between D. hansenii and several lactic acid and coryneform bacteria, including those we isolated from fermenting tobacco. These microbial consortia are typical of certain fermenting substrates that are characterized by a low C/N ratio, such as ripening cheeses (2,4,10,31,36,43,61), fresh sausages (7,47), vegetables (35), and algae (57). An association between D. hansenii and P. pentosaceus, revealed for tobacco samples (Tables 4 and 5), has previously been described for sorghum fermentation (35), and the same yeast has been isolated from the surface microflora of many brick cheeses in association with several coryneform bacteria, including C. ammoniagenes (58).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy is the specificity of the association between D. hansenii and several lactic acid and coryneform bacteria, including those we isolated from fermenting tobacco. These microbial consortia are typical of certain fermenting substrates that are characterized by a low C/N ratio, such as ripening cheeses (2,4,10,31,36,43,61), fresh sausages (7,47), vegetables (35), and algae (57). An association between D. hansenii and P. pentosaceus, revealed for tobacco samples (Tables 4 and 5), has previously been described for sorghum fermentation (35), and the same yeast has been isolated from the surface microflora of many brick cheeses in association with several coryneform bacteria, including C. ammoniagenes (58).…”
Section: Discussionmentioning
confidence: 99%
“…V3 region of the bacterial 16S rRNA gene and the D1 region of eukaryotic 26s rRNA gene taken from the microbial population in the milk of cheese and in the traditional blue veined Spanish cheese made by using rennet extract were analyzed and aimed to be identified. El-Baradei et al (2007) Cocolin et al (2004) identified Clostridium spp in Late Blowing cheese samples by using PCR-DGGE method. They determined Clostridium spp.…”
Section: Non-culture-based Molecular Methodsmentioning
confidence: 99%
“…Enzyme profiling of 14 representative LAB isolates found in Sao Jorge traditional cheese (from Kongo et al, 2007). Molecular biology (genotypic) methods (Figure 12) on the other hand -largely DNA-based techniques -offer much greater discriminatory power, all the way to differentiation of individual strains (Aymerich et al, 2006, Cocolin et al, 2004, Furet et al, 2004, Prabhakar et al, 2011. Thus, a combination of both phenotypic and genotypic identification techniques (so called polyphasic approach) is preferred (Temmerman et al, 2004, Aquilanti et al, 2006.…”
Section: Characteristicsmentioning
confidence: 99%